Exploring Challenges, Strategies, and Human Impacts of Bilingual Class in Indonesian Secondary School - Muhammad Dalimunte; Farida Repelita Waty BR Kembaren; Zamzami Zamzami (Journal of General Education and Humanities, 2026)
Bilingual learning has been increasingly implemented in Indonesian secondary schools to enhance students’ English proficiency and global competitiveness; however, its classroom implementation remains uneven and challenging. This study aims to explore the challenges, instructional strategies, and human impacts of bilingual learning in everyday school practices. Employing a qualitative case study approach, the research was conducted at SMPS Iskandar Muda Aceh Utara through classroom observations and semi-structured interviews with teachers, students, and school administrators. The findings reveal that bilingual learning encounters interconnected challenges at multiple levels, including students’ limited academic English proficiency, teachers’ pedagogical and linguistic constraints, and insufficient institutional and policy support. Although many students demonstrate conceptual understanding, they often struggle to articulate academic ideas in English, while teachers struggle to balance content mastery and language use. To address these challenges, teachers and schools adopt adaptive strategies such as code-switching, scaffolding, flexible language practices, and gradual implementation of bilingual instruction. Beyond instructional outcomes, the study highlights significant human impacts, particularly on students’ motivation, socio-emotional development, and classroom engagement. Initial anxiety and hesitation are commonly observed; however, supportive instructional practices foster increased confidence, resilience, and active participation over time. This study concludes that bilingual learning should be understood not merely as a technical instructional model, but as a human-centered educational practice shaped by linguistic readiness, emotional dynamics, and institutional context.